I need to know - Anthony, Marc; Rooney, Cory; Sony Music Entertainment (New York : Sony Music Entertainment, 1999)
Contains two different versions of the single.
CD 1 : Single version / (3:31) -- Album version / (3:50).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Rock music -- 1991-2000.; Popular music -- 1991-2000.